2000
DOI: 10.1103/physrevb.61.1748
|View full text |Cite
|
Sign up to set email alerts
|

Rumpled relaxation of TiC(001) and TaC(001) determined by high-resolution medium-energy ion scattering spectroscopy

Abstract: The rumpled relaxations of TiC͑001͒ and TaC͑001͒ with strong covalent bonds were determined precisely by medium energy ion scattering using a toroidal electrostatic analyzer with an excellent energy resolution of ⌬E/Eϭ9ϫ10 Ϫ4 . It allows a monolayer depth resolution and thus a simple triangulation method using the ion shadowing effect achieved the accuracy of 0.01 Å in depth for the displacement of atoms near a surface region. The surface relaxation ͑ϩ: outwards͒ and rumpling ͓ϩ: displacement of C toward vacuu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
11
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 18 publications
5
11
1
Order By: Relevance
“…[34][35][36][37][38] The stability of the three low-index Miller surfaces has been studied in detail for HfC, 39 which is consistent with previous theoretical studies for the HfC surfaces 40,41 that the (001) surface is the most stable one. These calculations have provided a large number of insights and helped to answer the long standing questions about the interpretation of experimental measurements.…”
Section: The Models and Calculation Detailssupporting
confidence: 71%
“…[34][35][36][37][38] The stability of the three low-index Miller surfaces has been studied in detail for HfC, 39 which is consistent with previous theoretical studies for the HfC surfaces 40,41 that the (001) surface is the most stable one. These calculations have provided a large number of insights and helped to answer the long standing questions about the interpretation of experimental measurements.…”
Section: The Models and Calculation Detailssupporting
confidence: 71%
“…First, we obtained the surface energies for the (0 0 1) face of MX phases in a good agreement with previous pseudopotential plane-wave-based DFT results (Table 1). We found that c s is higher for (0 0 1)MC than for (0 0 1 As obtained in numerous theoretical [29,[35][36][37][38][39][40][41][42][43] and experimental [44][45][46][47][48] studies as well as demonstrated in our calculations (Table 1), the free MX(0 0 1) surface exhibits a rippled relaxation, where the topmost X and M atoms are displaced outward and inward with respect to the atomic positions in bulk. The displacements of X atoms (d X ) are less than those of M atoms (d M ) in all MX except for the Group V TM nitrides (VN, NbN, and TaN).…”
Section: Surface Properties Of (0 0 1)mxcontrasting
confidence: 39%
“…42,43) For the transition metal nitrides and carbides, outward displacement of anion was reported from the first-principles calculations, 44,45) which is consistent with the previous experiments. 46) In case of oxides such as MgO, outward displacement of O has been reported by theory [47][48][49] and experiments. 50) However, surface rumpling of monoxide is too small to measure, especially for the stable (001) surface.…”
Section: Relaxation and Rumplingmentioning
confidence: 95%